Freedom dreaming to STEM: A conceptual model for Black youth’s racial and STEM identity development through social media - LeBlanc, Tate; Loyd, Aerika Brittian (Frontiers in Psychology, 2022)
Social media use has become increasingly enmeshed in the lives of youth. Although investigations in this area have tended to focus on risk (e.g., cyberbullying) and negative outcomes (e.g., in mental health and academic functioning), a growing body of literature suggests there may be positive developmental outcomes associated with Black youths’ social media use. Social media may offer Black youth a means of resisting negative experiences, expand their opportunities to create and explore, and facilitate the integration of their racial and STEM identities. Aligned with PYD perspectives and PVEST, we suggest this dynamic process occurs iteratively within youth and bidirectionally between youth and their environment (online and offline) over the course of development. In this article, we present a conceptual model to guide future investigations to address gaps in the literature and elucidate the linkages between social media use, racial identity, and STEM identity among Black youth. We begin by reviewing two frameworks that provide the theoretical foundations for our model. We then discuss our outcomes of interest: racial identity and STEM identity. Given its rapidly evolving nature, we then proceed with a discussion about how social media may be operationalized, noting limitations in the current literature and highlighting the unique ways in which social media differs from offline contexts. Subsequently, we present our conceptual model, which we situate within distal, proximal, and individual offline influences. We also propose mechanisms that may link social media use to positive identity outcomes. We conclude this article with recommendations for future investigations.